The Effects of Exchange Rate Change on the Trade Balance of Slovakia - Jana Šimáková (European Financial and Accounting Journal, 2014)
This paper empirically investigates the impact of change in exchange rate on export and import flows between Slovakia and its major trading partners. Devaluation or depreciation of a currency worsens the trade balance before improving it, resulting in a J-curve pattern. For the purpose of this paper, aggregated and disaggregated approaches are used. This paper investigates J-curve phenomenon using quarterly time series data over the period 1997:1 to 2013:4. The results provide evidence that the classical J-curve effect does not exist in Slovakia on the aggregated level. Instead, currency depreciation (increase in real effective exchange rate) is accompanied only by positive change in trade balance with no deterioration under initial value. On the bilateral level, there exists J- curve in trade with Hungary.
Keywords: F10; F14; F31; 650; Trade balance; J-curve; International trade; Exchange rate; Cointegration